Current Insights Into the Role of Neuropeptide Y in Skin Physiology and Pathology - Anderson, Zoya T.; Dawson, Alex D.; Slominski, Andrzej T.; Harris, Melissa L. (Frontiers in Endocrinology, 2022)
Neuropeptide Y is widely distributed within the body and has long been implicated as a contributor to skin disease based on the correlative clinical data. However, until recently, there have been few empirical investigations to determine whether NPY has a pathophysiological role in the skin. Due to appearance-altering phenotypes of atopic dermatitis, psoriasis, and vitiligo, those suffering from these diseases often face multiple forms of negative social attention. This often results in psychological stress, which has been shown to exacerbate inflammatory skin diseases – creating a vicious cycle that perpetuates disease. This has been shown to drive severe depression, which has resulted in suicidal ideation being a comorbidity of these diseases. Herein, we review what is currently known about the associations of NPY with skin diseases and stress. We also review and provide educated guessing what the effects NPY can have in the skin. Inflammatory skin diseases can affect physical appearance to have significant, negative impacts on quality of life. No cure exists for these conditions, highlighting the need for identification of novel proteins/neuropeptides, like NPY, that can be targeted therapeutically. This review sets the stage for future investigations into the role of NPY in skin biology and pathology to stimulate research on therapeutic targeting NPY signaling in order to combat inflammatory skin diseases.